2014
DOI: 10.1136/jmedgenet-2014-102396
|View full text |Cite
|
Sign up to set email alerts
|

Temple syndrome: improving the recognition of an underdiagnosed chromosome 14 imprinting disorder: an analysis of 51 published cases

Abstract: Chromosome 14 harbours an imprinted locus at 14q32. Maternal uniparental disomy of chromosome 14, paternal deletions and loss of methylation at the intergenic differentially methylated region (IG-DMR) result in a human phenotype of low birth weight, hypotonia, early puberty and markedly short adult stature. The analysis of the world literature of 51 cases identifies the key features that will enhance diagnosis and potentially improve treatment. We found a median birth weight SD score (SDS) of -1.88 and median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
201
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(218 citation statements)
references
References 38 publications
9
201
0
8
Order By: Relevance
“…Until recently, TS14 was regarded as a differential molecular diagnosis of Prader-Willi syndrome (PWS), but the broadening of genetic testing shows that the TS14 phenotype is heterogeneous, overlaps in early childhood with that of SRS, and is not mandatorily associated with (mild) psychomotoric retardation [21]. The impressive result of the application of multilocus tests in ID diagnostics is therefore obvious as a growing number of patients with Temple syndrome (TS14) can be identified among patients referred as SRS [22].…”
Section: Limitation 3: Ambiguous Findings In Idsmentioning
confidence: 99%
“…Until recently, TS14 was regarded as a differential molecular diagnosis of Prader-Willi syndrome (PWS), but the broadening of genetic testing shows that the TS14 phenotype is heterogeneous, overlaps in early childhood with that of SRS, and is not mandatorily associated with (mild) psychomotoric retardation [21]. The impressive result of the application of multilocus tests in ID diagnostics is therefore obvious as a growing number of patients with Temple syndrome (TS14) can be identified among patients referred as SRS [22].…”
Section: Limitation 3: Ambiguous Findings In Idsmentioning
confidence: 99%
“…In a comprehensive review of 51 published cases, Ioannides et al [2] showed that patients with Temple syndrome have reduced pre- and postnatal growth, hypotonia, facial dysmorphia, small feet and hands, and short stature in addition to precocious puberty. Additionally, half of patients with Temple syndrome are obese.…”
Section: Introductionmentioning
confidence: 99%
“…There are additionally some dysmorphic characteristics associated with TS, specifically a characteristic face with a broad nose and high forehead, and small hands and feet. The most common molecular cause of TS reported to date is maternal uniparental disomy of chromosome 14, but loss of methylation of IG-DMR and paternal deletions have also been reported (summarised in Ioannides et al (2014)). All of these perturbations would be predicted to reduce the expression dosage of the protein-encoding genes and increase that of the ncRNAs (Fig.…”
Section: Human Upd(14) Syndromesmentioning
confidence: 99%
“…The 51 cases of TS published to date have been summarised in a recent clinical review (Ioannides et al 2014). This syndrome is characterised by intrauterine growth restriction (placental insufficiency has been reported), commonly followed by hypotonia and perinatal failure to thrive.…”
Section: Human Upd(14) Syndromesmentioning
confidence: 99%